Faktor-faktor yang mempengaruhi penglibatan pelajar dalam perbincangan atas talian - Nur Fatin, binti Yahaya (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This research was aimed to investigate the factors that influence involvement of students from Faculty of Cognitive Sciences and Human Development in the online discussion. The total of 100 students from the Faculty of Cognitive Sciences and Human Development was chosen to be respondents in this research. The students were chosen by different course to get better result of research which are from Bachelor of Science (Hons) in Cognitive Science, Bachelor of Science (Hons), Human Resource Development and Counselling Bachelor (Hons). Research was conducted using quantitative methods. Based on research, the results that obtained through this research, we found that there are two factors that affect student engagement and student satisfaction using online discussion. As a conclusion, as a good educator by giving feedback and provide a knowledge for online learning resources will encourage the students to using online discussion. Besides, learning environments also plays an important role for students to engage using in online discussion for their better learning session.